Gene expression profile of ABC transporters and cytotoxic effect of ibuprofen and acetaminophen in an epithelial ovarian cancer cell line in vitro - Renilton Aires Lima; Eduardo Batista Cândido; Flávia Perrim de Melo; Josiane Barbosa Piedade; Paula Vieira Teixeira Vidigal; Luciana Maria Silva; Agnaldo Lopes da Silva Filho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSES: To determine the basic expression of ABC transporters in an epithelial ovarian cancer cell line, and to investigate whether low concentrations of acetaminophen and ibuprofen inhibited the growth of this cell line in vitro. METHODS: TOV-21 G cells were exposed to different concentrations of acetaminophen (1.5 to 15 μg/mL) and ibuprofen (2.0 to 20 μg/mL) for 24 to 48 hours. The cellular growth was assessed using a cell viability assay. Cellular morphology was determined by fluorescence microscopy. The gene expression profile of ABC transporters was determined by assessing a panel including 42 genes of the ABC transporter superfamily. RESULTS: We observed a significant decrease in TOV-21 G cell growth after exposure to 15 μg/mL of acetaminophen for 24 (p=0.02) and 48 hours (p=0.01), or to 20 μg/mL of ibuprofen for 48 hours (p=0.04). Assessing the morphology of TOV-21 G cells did not reveal evidence of extensive apoptosis. TOV-21 G cells had a reduced expression of the genes ABCA1, ABCC3, ABCC4, ABCD3, ABCD4 and ABCE1 within the ABC transporter superfamily. CONCLUSIONS: This study provides in vitro evidence of inhibitory effects of growth in therapeutic concentrations of acetaminophen and ibuprofen on TOV-21 G cells. Additionally, TOV-21 G cells presented a reduced expression of the ABCA1, ABCC3, ABCC4, ABCD3, ABCD4 and ABCE1 transporters.